Blending of polycaprolactone with polyvinyl chloride polymers using silica gel as a functional reinforcement - Mohammed, Kathrin Sleman; Coskun, Meltem; Babakr, Karukh Ali; Kok, Mediha; Qader, Ibrahim Nazem (Springer, 2025)
Polymer nanocomposites reinforced with inorganic fillers offer a promising approach to tailoring functional properties for advanced optoelectronic and photonic devices. This study investigates the influence of silica gel incorporation on the structural, thermal, and optical behavior of a polycaprolactone (PCL):polyvinyl chloride (PVC) blend prepared in equal ratios using the solvent casting method. Silica gel was added in concentrations from 0 to 40 wt%, and its effects were systematically examined. X-ray diffraction (XRD) confirmed reduced crystallinity with increasing silica due to disruption of polymer chain packing. Differential scanning calorimetry (DSC) revealed a glass transition temperature of the pristine blend at similar to 55.26 degrees C, which shifted slightly with silica loading, reflecting filler-polymer interactions. Thermogravimetric analysis (TGA) demonstrated multi-step decomposition: initial weight loss below 273 degrees C from moisture/solvent release (similar to 5%), followed by major polymer degradation between 273 and 490 degrees C attributed to PCL chain scission and PVC dehydrochlorination. Residual silica particles enhanced thermal resistance at higher temperatures. Fourier-transform infrared spectroscopy (FTIR) indicated hydrogen bonding between silica silanols and PCL carbonyls, while UV-Vis spectroscopy showed band gap reduction with filler content, with the direct allowed band gap decreasing from 4.2 eV (Si0) to 4.0 eV (Si40). Dielectric studies confirmed enhanced polarization at higher filler concentrations, linked to interfacial effects and defect states. Overall, silica gel reinforcement improved thermal stability, altered structural order, and tuned optical properties, underscoring the suitability of PCL:PVC/silica composites for applications in solar cells, photodetectors, and light-emitting devices.
Keywords: Scanning Calorimetry; Magnetic-Properties; Nanocomposite; Nanoparticles; Sio2